Innovation of Prototype of Stunting Health Information System and 3D Pageflip E-Module on Stunting Preventive Knowledge and Attitude in South Tangerang - Rita Dwi Pratiwi; Riris Andriati; Fenita Purnama Sari Indah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
According to an analysis conducted by the World Bank Group, WHO, and UNICEF, around 144 million children who are under the age of five (21.3%) were affected by stunting worldwide in 2019. By 2022, this figure had risen to an estimated 148.1 million children (22.3%). This study aims to evaluate the health promotion interventions utilizing a prototype of a stunting health information system and a 3D pageflip e-module in enhancing attitudes and knowledge for the prevention of stunting in South Tangerang. This study applied a quantitative approach combined with a quasi-experimental design, utilizing a two-group design with a pretest and post-test measurements framework. A total of 106 individuals surveyed were included, divided equally into two groups: one group received the prototype stunting health information system intervention, and the other was provided with the 3D Pageflip e-module, comprising 53 participants for every group. The Wilcoxon test showed the prototype of the stunting health information system group showed a significant difference for knowledge (p = 0.046) and attitude (p = 0.025), and the 3D pageflip e-module group showed a significant difference in knowledge and attitude (p = 0.000). The Mann-Whitney test showed that there was a significant difference for knowledge (p = 0.000) and for attitude (p = 0.042). The effect size test for knowledge is 1.06 and for attitude 0.27. It can be concluded that the prototype of the stunting health information system and the 3D pageflip e-module effectively increase mothers' knowledge and attitudes regarding stunting prevention. Keywords: Prototype, Stunting Health Information System, 3D Pageflip E Module, Knowledge, Preventive, Attitude